Comparative analysis of the long-term effect of two families of high-flux polysulfone dialysers on platelet count: a retrospective cross-sectional study - Del Giorno R; Berwert L; Pianca S; Bianchi G; Giannini O; Gabutti L (Dove Medical Press, 2017)
Rosaria Del Giorno,1 Lorenzo Berwert,1 Silvio Pianca,2 Giorgia Bianchi,3 Olivier Giannini,4 Luca Gabutti1 1Department of Internal Medicine, Nephrology and Dialysis Unit, Regional Hospital of Bellinzona and Valli, Ente Ospedaliero Cantonale, Bellinzona, 2Nephrology Unit, Civico Hospital, Ente Ospedaliero Cantonale, Lugano, 3Nephrology Unit, La Carità Hospital, Ente Ospedaliero Cantonale, Locarno, 4Nephrology Unit, Beata Vergine Hospital, Ente Ospedaliero Cantonale, Mendrisio, Switzerland Introduction: Thrombocytopenia is a potential complication of hemodialysis (HD), and its occurrence has been described even with highly biocompatible polysulfone (PSf) membranes. Dialysis units routinely monitor platelet (PLT) count at the beginning of HD sessions. However, considering that the long-term effects on PLT count could easily be missed, the prevalence of HD-related thrombocytopenia could be underestimated. In the present study, we aimed to investigate the following: 1) the long-term impact of HD treatment on PLT count, comparing two families of dialysis membranes made up of similar PSfs; 2) whether the switch between the dialysis membranes studied significantly affects PLT count; and 3) the prevalence and the risk of HD-induced thrombocytopenia according to the dialysis membranes used. Methods: A cross-sectional retrospective study was performed comprising 157 adult chronic HD patients. The HD membranes under investigation were of the series FX, Helixone® Fresenius (Filters A), and Polyflux® Gambro (Filters B). Patients were treated in 4 dialysis units in Southern Switzerland. Data were collected from a centralized computing platform. Findings: PLT count significantly differs between Filters A and B with, respectively, 188 (153–243) ×10E9/L versus 214 (179–255) ×10E9/L (p=0.036). The prevalence of thrombocytopenia was higher for Filter A compared with Filter B (28.4% versus 12.8%; p<0.001). The switch from Filter A to Filter B significantly affected PLT count: from 189 (146–217) ×10E9/L to 217 (163–253) ×10E9/L (p<0.001; analysis on 26 patients). A linear random-intercept model confirmed the results (β coefficient =35.214; SE =5.956; p<0.001). In a mixed-effects logistic regression model, the risk of thrombocytopenia for Filter B was 0.157 (CI =0.056–0.442). Discussion: Our data suggest that among the PSf membranes studied, the FX membrane induced a lasting decrease in PLT count and caused significantly more thrombocytopenia. Prospective studies are warranted to verify our findings. Keywords: comparative analysis, polysulfone membranes, platelet count, retrospective pilot study, thrombocytopenia